Tuition Fee Controversy: Reaching Break Even Point Without Sacrificing Accessibility for Students from Low-Income Families - Muhammad Nur Ahsan; Sholihin; Moh. Qoyum; Nur Anim Jauhariyah (ICO EDUSHA, 2024)
This study analyzes how the controversy over the determination of tuition fees, including the amount, the mechanism of relief/scholarships, and its impact on accessibility, affects the achievement of BEP. A qualitative case study was conducted at a Madrasah Tsanawiyah (MTs) in Banyuwangi, East Java, affiliated with the Ma'arif educational organization. Data were collected through non-participatory observation, semi-structured and in-depth interviews using the snowball sampling technique, and document analysis. The results show that the amount of tuition fees that are too high or too low both hinder BEP. Non-transparent relief/scholarship mechanisms reduce public trust, while effective mechanisms increase accessibility without disrupting the institution's income. This study also identifies alternative financing models such as diversifying revenue sources through facility rentals, optimizing operational efficiency, and partnering with the private sector as potential solutions. Factors for the successful implementation of alternative models include leadership commitment, transparency, community participation, policy support, and management capacity. This study provides recommendations for educational institutions and the government in formulating fair, effective, and sustainable financing policies.